Correlation between antigenemia of Paracoccidioides brasiliensis and inhibiting effects of plasma in patients with paracoccidioidomycosis - Sugizaki, M. F.; Peracoli, M. T. S.; Mendes-Giannini, Maria José Soares [UNESP]; Soares, A. M. V. C.; Kurokawa, C. S.; Mendes, R. P.; Marques, S. A.; Freire-Maia, D. V. (B I O S Scientific Publishers Ltd, 1999)
Metabolites produced by pathogenic fungi may be involved in the pathogenesis of fungal infections consequently altering the defence mechanisms of the host. In this study the levels of Paracoccidioides brasiliensis antigens detected in the plasma of patients with paracoccidioidomycosis correlated with the suppression index detected by the low mitogenic response of peripheral blood mononuclear cells (PBMC) to phytohaemaglutinin (PHA). This inhibitory effect on lymphoproliferation was observed in the plasma of 58% of the patients, suggesting the presence of inhibitory factors. Plasma samples from paracoccidioidomycosis patients having or not having inhibitory factors showed no significant effect on chromosomes of lymphocytes from healthy individuals, However, these plasmas had a suppressive activity on the blastogenic response of these lymphocytes stimulated with PHA, that was independent of a cytotoxic effect. P. brasiliensis antigens added to the proliferative response of PBMC from healthy individuals stimulated or not stimulated with PHA showed a dose-dependent suppressor effect, reproducing the inhibitory effect of patients' plasma. We suggest that the antigens of P, brasiliensis present in the plasma of patients, even at low concentrations, can play an important role in the reduction of the cellular immune response and in the genesis of the immuneregulatory disturbances observed in paracoccidioidomycosis.
Keywords: antigenemia; paracoccidioidomycosis; plasma inhibitory factors